(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The Internet of Things (IoT) is a network of active and passive objects that interact with each other for information exchange. Due to the immense acceptance of the concept, the IoT utility rate has increased exponentially in recent years. Being an open (and sometimes not-physically-observed) network, the issue of data privacy and security becomes a severe concern on account of the presence of untrusted and malicious users on the network. Most of the existing security approaches are centralized in nature, which leads to bottlenecks and obscurity in public verifiability. Due to its functionality, Blockchain technology could be a solution to these problems, owing to its distributed immutable ledger that is cryptographically secured. In this research, we intend to address the security issues in terms of confidentiality, integrity, and access control mechanisms in the IoT for a healthcare system, where the data files of a particular patient are encrypted and stored on the public blockchain storage in a distributed fashion and accessed through smart contracts. We have observed the efficiency and time complexity of an IoT-based medical health care system with the utilization of Kovan, Binance Smart Chain, Rinkeby, and Matic Blockchain networks. The authors proposed a secure model for IoT-based healthcare systems with the incorporation of the blockchain network.